Cold pursuit [large type] - Mehl, Nancy (Mehl, Nancy. Ryland & St. Clair, 2023)
"Ex-FBI profiler River Ryland still suffers from PTSD after a case went horribly wrong. Needing a fresh start, she moves to St. Louis to be near her ailing mother and opens a private investigation firm with her friend and former FBI partner, Tony St. Clair. They're soon approached by a grieving mother who wants them to find out what happened to her teenaged son, who disappeared four years ago. River knows there's almost no hope the boy is still alive, but his mother needs closure, and River and Tony need a case, no matter how cold it might be. But as they follow the boy's trail, which gets more complicated at every turn, they find themselves in the path of a murderer determined to punish anyone who gets in his way. As River and Tony race to stop him before he kills again, an even more dangerous threat emerges, stirring up the past that haunts River and plotting an end to her future."--